Dynamics of fluctuations in the Gaussian model with conserved dynamics. (4th October 2019) - Corberi, Federico; Mazzarisi, Onofrio; Gambassi, Andrea
Abstract: We study the fluctuations of the Gaussian model, with conservation of the order parameter, evolving in contact with a thermal bath quenched from an initial inverse temperature to a final one . At every time there exists a critical value of the variance s of the order parameter per degree of freedom such that the fluctuations with are characterized by a macroscopic contribution of the zero wavevector mode, similarly to what occurs in an ordinary condensation transition. We show that the probability of fluctuations with, for which condensation never occurs, rapidly converges towards a stationary behavior. By contrast, the process of populating the zero wavevector mode of the variance, which takes place for, induces a slow non-equilibrium dynamics resembling that of systems quenched across a phase transition.